Novel CTRP8‐RXFP1‐JAK3‐STAT3 axis promotes Cdc42‐dependent actin remodeling for enhanced filopodia formation and motility in human glioblastoma cells. Issue 2 (18th June 2021) - Glogowska, Aleksandra; Thanasupawat, Thatchawan; Beiko, Jason; Pitz, Marshall; Hombach‐Klonisch, Sabine; Klonisch, Thomas
Abstract : C1q tumor necrosis factor‐related peptide 8 (CTRP8) is the least studied member of the C1Q‐TNF‐related peptide family. We identified CTRP8 as a ligand of the G protein‐coupled receptor relaxin family peptide receptor 1 (RXFP1) in glioblastoma multiforme (GBM). The CTRP8‐RXFP1 ligand–receptor system protects human GBM cells against the DNA‐alkylating damage‐inducing temozolomide (TMZ), the drug of choice for the treatment of patients with GBM. The DNA protective role of CTRP8 was dependent on a functional RXFP1‐STAT3 signaling cascade and targeted the monofunctional glycosylase N ‐methylpurine DNA glycosylase (MPG) for more efficient base excision repair of TMZ‐induced DNA‐damaged sites. CTRP8 also improved the survival of GBM cells by upregulating anti‐apoptotic BCl‐2 and BCL‐XL. Here, we have identified Janus‐activated kinase 3 (JAK3) as a novel member of a novel CTRP8‐RXFP1‐JAK3‐STAT3 signaling cascade that caused an increase in cellular protein content and activity of the small Rho GTPase Cdc42. This is associated with significant F‐actin remodeling and increased GBM motility. Cdc42 was critically important for the upregulation of the actin nucleation complex N‐Wiskott–Aldrich syndrome protein/Arp3/4 and actin elongation factor profilin‐1. The activation of the RXFP1‐JAK3‐STAT3‐Cdc42 axis by both RXFP1 agonists, CTRP8 and relaxin‐2, caused extensive filopodia formation. This coincided with enhanced activity of ezrin, a key factor in tethering F‐actin to the plasma membrane, and inhibition of the actin filament severing activity of cofilin. The F‐actin remodeling and pro‐migratory activities promoted by the novel RXFP1‐JAK3‐STAT3‐Cdc42 axis were blocked by JAK3 inhibitor tofacitinib and STAT3 inhibitor STAT3 inhibitor VI. This provides a new rationale for the design of JAK3 and STAT3 inhibitors with better brain permeability for clinical treatment of the pervasive brain invasiveness of GBM. Abstract : The C1Q‐TNF‐related peptide family member C1q tumor necrosis factor‐related peptide 8 (CTRP8) and its G protein‐coupled receptor relaxin family peptide receptor 1 (RXFP1) are emerging as a novel ligand–receptor system that can protect glioblastoma cells against DNA‐alkylating damage and apoptosis. We describe a novel CTRP8‐RXFP1‐Janus‐activated kinase 3‐STAT3 signaling cascade that enhances cellular protein content and activity of small Rho GTPase Cdc42, which directs F‐actin cytoskeletal remodeling, filopodia formation, and increased glioblastoma multiforme migration.